E-commerce adoption among micro agri-business enterprise in Longsheng, China: The moderating role of entrepreneurial orientation - Li, Hanfang; Liow, Guateng; Yuan, Shengjun (Frontiers in Psychology, 2022)
E-commerce in agri-business enterprises is a potent force in eradicating rural poverty in China. However, it has not reached its potential as many of the agri-business enterprises in rural areas are slow in re-thinking their distribution channel and implement e-commerce. This study utilizes the multidimensionality of the Tornatsky and Fleisher Technology-Organization-Environment (TOE) framework to provide insights into why rural agri-business enterprises are not adopting e-commerce strategies. Specifically, it examines the moderating role of entrepreneurial orientation (EO) on the relationship between the sub-variables in the three contexts and e-commerce adoption. Empirical data from 192 micro agri-business enterprises were analysed using PLS-SEM. The results show that relative advantage, organization readiness, competitive pressure and government support have a direct positive impact on e-commerce adoption except cost. The results also show that EO does not have a significant role in moderating the variables in the organizational context and environmental context. EO only moderated the relationship between relative advantage in the technology context and e-commerce adoption. This study advances research on e-commerce adoption by highlighting the importance of the owners’ EO as a moderator between TOE factors and e-commerce adoption. It suggests that entrepreneurship must be pursued vigorously among agribusiness owners in rural China to enhance the adoption of e-commerce.